Tenascin-C modulates matrix contraction via focal adhesion kinase- and Rho-mediated signaling pathways. - Midwood, K; Schwarzbauer, J (2002)
A provisional matrix consisting of fibrin and fibronectin (FN) is deposited at sites of tissue damage and repair. This matrix serves as a scaffold for fibroblast migration into the wound where these cells deposit new matrix to replace lost or damaged tissue and eventually contract the matrix to bring the margins of the wound together. Tenascin-C is expressed transiently during wound repair in tissue adjacent to areas of injury and contacts the provisional matrix in vivo. Using a synthetic model of the provisional matrix, we have found that tenascin-C regulates cell responses to a fibrin-FN matrix through modulation of focal adhesion kinase (FAK) and RhoA activation. Cells on fibrin-FN+tenascin-C redistribute their actin to the cell cortex, downregulate focal adhesion formation, and do not assemble a FN matrix. Cells surrounded by a fibrin-FN+tenascin-C matrix are unable to induce matrix contraction. The inhibitory effect of tenascin-C is circumvented by downstream activation of RhoA. FAK is also required for matrix contraction and the absence of FAK cannot be overcome by activation of RhoA. These observations show dual requirements for both FAK and RhoA activities during contraction of a fibrin-FN matrix. The effects of tenascin-C combined with its location around the wound bed suggest that this protein regulates fundamental processes of tissue repair by limiting the extent of matrix deposition and contraction to fibrin-FN-rich matrix in the primary wound area.